Chronic undernutrition and traditional weaning foods are associated with fat stores in ariaal infants of Northern Kenya. Issue 2 (22nd November 2013) - Miller, Elizabeth M.
ABSTRACT The high proportion of human infant fat is hypothesized to protect infant brains by mobilizing against growth disturbances caused by acute nutritional and pathogen stress during weaning. However, individuals who experience chronic nutritional stress have been shown to store fat rather than mobilize fat stores, although this has not been demonstrated during infancy. This study investigated the relationship between fat development, diet, and nutritional status among 239 breastfeeding Ariaal infants, a group of settled pastoralists who experience both acute and chronic nutritional stress residing in Marsabit District, Kenya. This study had three goals: 1) To investigate the pattern of fat accumulation among Ariaal infants compared with a reference population; 2) to explore the relationship between chronic nutritional stress and fat deposits; and 3) to determine the relationship between traditional weaning foods, particularly cow's milk, and infant's fat. Infants, particularly infants experiencing chronic nutritional stress, were found to accumulate fat deposits in a manner that suggests reduced oxidation of fat stores. Infant upper arm fat area significantly increases with age over the weaning period compared with reference populations, who show a decline in body fat. Chronically undernourished infants were particularly likely to have increased levels of upper arm fat compared with normal infants or acutely undernourished infants. In addition, infants who consume cow's milk are significantly fatter than those that do not. These results suggest that Ariaal infants have both physiological and cultural mechanisms for fat storage in the face of their nutritionally stressed environment. Am J Phys Anthropol 153:286–296, 2014. © 2013 Wiley Periodicals, Inc.